La déesse intouchable : une Vierge andalouse - Antoinette Molinié (Mélanges de la Casa de Velázquez)
If “touching the object transcends” as proposed in the statement of the problem, an object’s transcendence will more often than not stem from its untouchability. It is in the light of this hypothesis of “touching by default” that we examine the adoration of the Virgen del Rocío in Andalusa. We look first at the processes whereby the image of the Virgin is rendered untouchable. However, there are certain objects which afford access to the goddess. We look at two types of such objects. One type may be defined as metonymies, the other as substitutes. The construction of these objects, combined with the untouchability of her image, confers on the goddess a power that transcends the limits of ecclesiastical authority.